Broad Purpose Vector for Site-Directed Insertional Mutagenesis in Bifidobacterium breve - Hoedt, Emily C.; Bottacini, Francesca; Cash, Nora; Bongers, Roger S.; van Limpt, Kees; Ben Amor, Kaouther; Knol, Jan; MacSharry, John; van Sinderen, Douwe (Frontiers in Microbiology, 2021)
Members of the genus Bifidobacterium are notoriously recalcitrant to genetic manipulation due to their extensive and variable repertoire of Restriction-Modification (R-M) systems. Non-replicating plasmids are currently employed to achieve insertional mutagenesis in Bifidobacterium. One of the limitations of using such insertion vectors is the presence within their sequence of various restriction sites, making them sensitive to the activity of endogenous restriction endonucleases encoded by the target strain. For this reason, vectors have been developed with the aim of methylating and protecting the vector using a methylase-positive Escherichia coli strain, in some cases containing a cloned bifidobacterial methylase. Here, we present a mutagenesis approach based on a modified and synthetically produced version of the suicide vector pORI28 (named pFREM28), where all known restriction sites targeted by Bifidobacterium breve R-M systems were removed by base substitution (thus preserving the codon usage). After validating the integrity of the erythromycin marker, the vector was successfully employed to target an α-galactosidase gene responsible for raffinose metabolism, an alcohol dehydrogenase gene responsible for mannitol utilization and a gene encoding a priming glycosyltransferase responsible for exopolysaccharides (EPS) production in B. breve. The advantage of using this modified approach is the reduction of the amount of time, effort and resources required to generate site-directed mutants in B. breve and a similar approach may be employed to target other (bifido)bacterial species.